Digitalisasi Manajemen Dokumen Terintegrasi Berbasis Sistem Informasi pada Perusahaan Logistik: Tinjauan dari Sisi Spesifikasi dan Arsitektur - Muhammad Fadhiel Alie; Dana Indra Sensuse; Faradillah Faradillah (Jurnal Informatika Global)
Multi Artha Sarana Solusi Inc. (MASS Cargo) is a logistic company providing freight forwarder service. MASS Cargo has a business process of service sales prioritizing lead time delivery. Another thing that becomes the main focus of the company’s business process is the quickness of document & administration report collection. However, it becomes the main problem faced by MASS Cargo since it affects to the delayed of invoice billing to the customers, impacting on the company’s cash flow directly. This research does an information system specification design which will be used as the main system and be able to help the smoothness of the document collection & report. Analysis of the business process, document, and interview with the stakeholders is used as referrals in the designing so that the information system corresponds to company’s need. The methodology used in the information system specification design is Rational Unified Process (RUP). RUP disciplines done in this research are requirement and analysis & design on inception & elaboration phases with 3 iterations. The result of this research are artifact documents representing the needs of the MASS Cargo’s integrated document management information system and mockup collection that has been validated by the users. Keywords : Specification Design, Information System, Integrated Document, Rational Unified Process, MASS Cargo